2003
DOI: 10.1161/01.hyp.0000051890.68573.94
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Mediated Negative Regulation of Npr1 Promoter Activity and Gene Transcription

Abstract: Abstract-Atrial natriuretic peptide receptor A (NPRA) plays important role(s) in the control of extracellular fluid volume and blood pressure homeostasis. We have determined and analyzed the functional promoter region of Npr1 gene (coding for NPRA) and studied the effect of angiotensin (Ang) II on its promoter activity and expression in cultured mouse mesangial cells. The promoter analysis of Npr1 gene revealed the presence of positive regulatory cis-elements in the regions Ϫ1982 to Ϫ1841 bp and Ϫ916 to Ϫ496 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Garg and Pandey 22 reported the transcriptional downregulation of Npr1 by angiotensin (Ang) II, confirming the mutual crossregulation of the two vasoactive hormones Ang II (vasoconstrictive) and ANP (vasodilatory) in the pathway mediating the pathophysiology of hypertension. Interestingly, we recently showed that the activity of the cGMP-RE was inhibited in spontaneously hypertensive rats.…”
Section: Perspectivesmentioning
confidence: 85%
“…Garg and Pandey 22 reported the transcriptional downregulation of Npr1 by angiotensin (Ang) II, confirming the mutual crossregulation of the two vasoactive hormones Ang II (vasoconstrictive) and ANP (vasodilatory) in the pathway mediating the pathophysiology of hypertension. Interestingly, we recently showed that the activity of the cGMP-RE was inhibited in spontaneously hypertensive rats.…”
Section: Perspectivesmentioning
confidence: 85%
“…This vitamin D-dependent induction of NPR-A expression may account for at least some of the salutary effects of vitamin D in the cardiovascular system. 71 NPR-A gene promoter activity has also been shown to be negatively regulated by angiotensin II 72 and positively regulated by osmotic stimuli. 73 The latter effect involves the endothelial NO synthase and p38 MAPK.…”
Section: Regulation Of the Np Receptorsmentioning
confidence: 99%
“…105 Two recent in vitro studies have indicated that GC-A gene transcription might be inhibited by Ang II and endothelin. 106,107 It has been suggested that local endothelin production mediates the effects of changes in extracellular tonicity on GC-A expression in the kidney. 107 Again, the relevance of these experiments to the in vivo situation needs to be confirmed.…”
Section: Regulation Of Gc-a At the Level Of Gene Transcriptionmentioning
confidence: 99%